Pengembangan LKPD Online Berbantuan Live Worksheet pada Materi Permutasi Kombinasi - Marlina, Marlina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop online learning media for student Worksheets (LKPD) assisted by Live Worksheets that are oriented to students' mathematical problem solving abilities in valid and practical permutations and combinations material. This media development process uses the ADDIE research and development model (analyze, design, develop, implement, and evaluate). The research subjects were 6 students of class XII SMK SMTI Bandar Lampung in the 2021/2022 academic year. The instruments used are in the form of a validation questionnaire, a teacher response questionnaire and a student response questionnaire. Based on the research, the data obtained from the validation results of online LKPD assisted by Live Worksheets by three validators got an average score of 76% with valid criteria, while the results of teacher and student responses related to the practicality of online LKPD obtained an average score of 88.15% and 84.82%. with practical criteria. In conclusion, online Worksheets with the help of Live Worksheets can be used as alternative media in learning to help improve students' mathematical problem solving abilities in combination permutation material. Keywords: Development, LKPD Online, Live Worksheet